Design and beam dynamics study of disk-loaded structure for muon LINAC. Issue 1 (1st January 2023) - Sumi, K; Iijima, T; Inami, K; Sue, Y; Yotsuzuka, M; Ego, H; Otani, M; Saito, N; Mibe, T; Yoshida, M; Kondo, Y; Moriya, K; et al.
Abstract: The disk-loaded structures (DLS) in the muon LINAC are under development for the J-PARC muon g–2/EDM experiment. Four DLSs with an accelerating gradient of 20 MV/m take charge of muon acceleration from 40 MeV to 212 MeV, which corresponds to 70% to 94% of the speed of light. The quasi-constant gradient type TM01-2π/3 mode DLSs with gradually varying disk spacing was designed and it was confirmed that the cumulative phase slip due to the mismatch between muon and phase velocity can be suppressed to less than 2 degrees at the frequency of 2592 MHz. In addition, the optimum synchronous phase and the lattice were investigated to satisfy the requirements of the total emittance less than 1.5π mm mrad and the momentum spread less than 0.1% in RMS.